Hierarchically Ordered Supramolecular Protein-Polymer Composites with Thermoresponsive Properties - Välimäki, Salla (Int J Mol Sci, 2015)
Synthetic macromolecules that can bind and co-assemble with proteins are important for the future development of biohybrid materials. Active systems are further required to create materials that can respond and change their behavior in response to external stimuli. Here we report that stimuli-responsive linear-branched diblock copolymers consisting of a cationic multivalent dendron with a linear thermoresponsive polymer tail at the focal point, can bind and complex Pyrococcus furiosus ferritin protein cages into crystalline arrays. The multivalent dendron structure utilizes cationic spermine units to bind electrostatically on the surface of the negatively charged ferritin cage and the in situ polymerized poly(di(ethylene glycol) methyl ether methacrylate) linear block enables control with temperature. Cloud point of the final product was determined with dynamic light scattering (DLS), and it was shown to be approximately 31 °C at a concentration of 150 mg/L. Complexation of the polymer binder and apoferritin was studied with DLS, small-angle X-ray scattering, and transmission electron microscopy, which showed the presence of crystalline arrays of ferritin cages with a face-centered cubic (fcc [Formula: see text]) Bravais lattice where lattice parameter a = 18.6 nm. The complexation process was not temperature dependent but the final complexes had thermoresponsive characteristics with negative thermal expansion.